Two years on, a perspective on MAFLD - Jacob George; Mohammed Eslam (eGastroenterology, 2023)
To provide clarity for research studies and clinical care, a set of positive criteria for adults and children with metabolic (dysfunction) associated fatty liver disease (MAFLD) was recently published and has subsequently been widely endorsed. The development and subsequent validation of the criteria for MAFLD has created a positive momentum for change. During the course of the ongoing discussion on the redefinition, some concerns have surfaced that we thought needs clarification. In this review, we provide a perspective on MAFLD and bringing clarity to some of the key aspects that have been recently raised.